An OS-Hypervisor Infrastructure for Automated OS Crash Diagnosis and Recovery in a Virtualized Environment - Jann, Joefon; Burugula, R. Sarma; Wu, Ching-Farn E.; Maghraoui, Kaoutar El (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
Recovering from OS crashes has traditionally been done using reboot or checkpoint-restart mechanisms. Such techniques either fail to preserve the state before the crash happens or require modifications to applications. To eliminate these problems, we present a novel OS-hyper visor infrastructure for automated OS crash diagnosis and recovery in virtual servers. Our approach uses a small hidden OS-repair-image that is dynamically created from the healthy running OS instance. Upon an OS crash, the hyper visor automatically loads this repair-image to perform diagnosis and repair. The offending process is then quarantined, and the fixed OS automatically resumes running without a reboot. Our experimental evaluations demonstrated that it takes less than 3 seconds to recover from an OS crash. This approach can significantly reduce the downtime and maintenance costs in data centers. This is the first design and implementation of an OS-hyper visor combo capable of automatically resurrecting a crashed commercial server-OS.